Awareness and perception about ragging amongst medical undergraduate students: a cross-sectional study - Suryawanshi, Jaya V.; Hazari, Madhavi (International Journal Of Community Medicine And Public Health, 2017)
Background: Several studies in the past have shown that abuse, bullying, harassment at educational institutions are a regular phenomenon; it is faced not only by medical students, but also other healthcare professionals. While research has been carried out on bullying, however, to our knowledge no research has been conducted as yet studying the perception of newly admitted medical undergraduate students about ragging. Hence the present study was aimed to assess the perception about ragging among undergraduate MBBS students. Methods: A cross-sectional study was conducted from August to October 2015 amongst 89 first year medical students of 2015 batch of ESIC Medical College, Kalaburagi, Karnataka, India. A pre-designed questionnaire which assessed perceptions regarding ragging amongst medical students was the tool of data collection. Results: Most of the male and female participants were unaware of fact that formal introduction is a type of ragging (72.73% and 98.21% respectively). We further inquired about student’s knowledge about provision of any legal action against ragging, majority of male and female students were unaware of any legal action (75% and 91% respectively). Conclusion: Overall awareness about ragging is not shown upto the mark. A prior education of students is utmost necessary. Provision of prior support for students may help to reduce anxiety among newcomers. There is need to develop awareness among these students about various aspects of ragging and legal action against it.